Evaluation of Bozem and Drainage Channels of Jade Hamlet Residential in Gresik - Jenny Caroline; Arintha Indah Dwi Syafiarti (Journal of Civil Engineering, Planning and Design, 2022)
Drainage refers to a vital component for water disposal so that a region or area can hinder potential puddle due to excessive water on the land surface. Therefore, a good plan adjusting the land condition of residential area belongs to a fundamental matter. Jade Hamlet Residence is located on Hulaan highway, Hulaan Urban Village, Menganti District, Gresik Regency, covering an area ±20 hectares and consisting of housing area, park, public facility, and catchment area. The drainage channel at this residence serves as the drainage for rain water and household dirty water disposal. During the rainy season in 2018 and 2019, the channel and bozem or drainage basin of this residence encountered overflowing and eventually caused puddle. To overcome this problem, the capacities of bozem and channel are in need of analysis and evaluation so as to figure out the runoff volume that can be accommodated in the bozem and investigate the discharge planned in the drainage channel by employing Log Person III method, chi-square distribution fit test, Kolmogorov-Smirnov test, rational formula, and exponential method. The results of analysis and evaluation demonstrated that the bozem capacity could not afford the runoff discharge (298.35 m3 309.55 m3), thereby demanding additional length and depth against the existing bozem. Meanwhile, the calculation of flood discharge planned for the drainage channels of S4.Ry3, S6.Ry1, S6.D1, S6.I2, S6.Cs1, S6.Rc1, S6.Rc2 indicate that they need redesigning by altering the channel dimension as the discharge capacity exceeds the channel.